Fibrous form-stable phase change materials with high thermal conductivity fabricated by interfacial polyelectrolyte complex spinning. (1st December 2020) - Fang, Hui; Lin, Jialin; Zhang, Lingjie; Chen, Anlin; Wu, Fangjuan; Geng, Lihong; Peng, Xiangfang
Graphical abstract: Highlights: PEG-based FSPCMs were fabricated by interfacial polyelectrolyte complex spinning. The negatively charged CNFs were cross-linked by the positively charged CS. CNF/CS networks prevented the leakage of PCMs during the phase change process. The FSPCM presented the maximum latent heat of 103 J/g and good stability. The thermal conductivity of the FSPCM could reach 4.005 W/mK at 47.5 wt% of BN-OH. Abstract: Polyethylene glycol (PEG)-based composite phase change materials (PCMs) containing hydroxylated boron nitride (BN-OH), cellulose nanofiber (CNF), and chitosan (CS) were prepared by the method of interfacial polyelectrolyte complex spinning, based on in-situ ionic cross-linking between CNF and CS. The wrapping effect of cross-linked CNF/CS networks and the strong interfacial interactions contributed to superior shape-stability throughout the phase change process. Furthermore, the homogeneously dispersed BN-OHs was beneficial to the construction of the continuous thermal conductive paths, and the excellent interfacial interactions between BN-OH and the matrix would lower the heat loss caused by phonon scattering in the interface. As a result, the thermal conductivity of the PCMs containing 47.5 wt% BN-OH reached 4.005 W/mK, which was 22.56 times higher than that of the pure PEG. Combined with the excellent thermal reliability and thermal stability, the form-stable PCMs showed a promising application potential in the fields of electronic cooling or temperature-adaptable textiles.